From Sustainability to Integrated Reporting: The Legitimizing Role of the CSR Manager. (December 2019) - Argento, Daniela; Culasso, Francesca; Truant, Elisa
This article aims to explore how an individual actor, embodying the role of the institutional entrepreneur, legitimizes new corporate reporting practices. This study is based on a longitudinal and explanatory case study of an Italian listed public utility, operating in the electricity sector, which has recently implemented Integrated Reporting. Findings were analysed through the lens of institutional entrepreneurship, revealing that Integrated Reporting can be implemented through the legitimizing activities carried out by the corporate social responsibility manager. This organizational professional, with strong competences and intrinsic engagement, efficiently uses available resources and gains support from various organizational groups through intense networking. A substantial change in corporate reporting practices can influence the position of the institutional entrepreneur who originally triggered the change process. The institutional entrepreneur first moves from the periphery to the centre of the organization and then shares such central role with other organizational professionals once the change has been implemented.